Experimental Validation of a New Modeling for the Design Optimization of a Sliding Vane Rotary Expander Operating in an ORC-Based Power Unit - Fabio Fatigati; Marco Di Bartolomeo; Davide Di Battista; Roberto Cipollone (Energies, 2020)
Sliding Rotary Vane Expanders (SVRE) are often employed in Organic Rankine Cycle (ORC)-based power units for Waste Heat Recovery (WHR) in Internal Combustion Engine (ICE) due to their operating flexibility, robustness, and low manufacturing cost. In spite of the interest toward these promising machines, in literature, there is a lack of knowledge referable to the design and the optimization of SVRE: these machines are often rearranged reversing the operational behavior when they operate as compressors, resulting in low efficiencies and difficulty to manage off-design conditions, which are typical in ORC-based power units for WHR in ICE. In this paper, the authors presented a new model of the machine, which, thanks to some specific simplifications, can be used recursively to optimize the design. The model was characterized by a good level of physical representation and also by an acceptable computational time. Despite its simplicity, the model integrated a good capability to reproduce volumetric and mechanical efficiencies. The validation of the model was done using a wide experimental campaign conducted on a 1.5 kW SVRE operated on an ORC-based power unit fed by the exhaust gases of a 3 L supercharged diesel engine. Once validated, a design optimization was run, allowing to find the best solution between two “extreme” designs: a “disk-shaped”—increasing the external diameter of the machine and reducing axial length—and by a “finger-shaped” machine. The predictions of this new model were finally compared with a more complex numerical model, showing good agreement and opening the way to its use as a model-based control tool.